KARAKTERISTIK MEKANIK KOMPOSIT SERAT BAMBU KONTINYU DENGAN PERLAKUAN ALKALI - Sofyan Djamil; Agustinus Purna Irawan (Program Studi Teknik Mesin Universitas Tarumanagara, 2018)
Abstract: Commonly used reinforcement materials are fibers, particles or flakes which have higher strength and modulus than matrix. Natural fibers of lignosellulose derived from natural resources such as bamboo, sisal, kenaf, hemp, wood and others are the largest raw materials found on earth, especially Indonesia. The reinforcement of natural fibers in composite materials has the advantage of good mechanical properties and is cheaper compared to synthetic fibers, using natural bamboo fiber, it can be made green composite .The research stages are bamboo raw material taken from the village of Pebasiran Parung Panjang BogorJawa Barat type bamboo apus (giganchtoloa apus), aged 3-4 years. Bamboo dried with surrounding air for 2 weeks, then cut with a knife manually, hinggga shaped-sized fiber; thickness 0.6 - 0.8 mm and width 6 - 8 mm. The 5% NaOH soaked fiber, for 72 hours, is dried at room temperature. Reinforcement using plain weave and twill weave type. Composite is made by hand lay up process, with thickness of 2 mm. Testing test is made with standard ASTM D3039 / D3039M-08, Observation of fiber structure with optical microscope. From research data and the calculation is then obtained for plain woven type before alkali treatment yield strength is 15.60 ± 2.24 MPa, after alkali treatment yield strength is 18.80 ± 2.13 MPa. For this type of woven twill before alkali treatment yield strength is 24.48 ± 3.92 MPa, after alkali treatment yield strength is 29.90 ± 2.27 MPa. For plain woven type before alkali treatment process the maximal tensile strength is 20.94 ± 3.69 MPa, after alkali treatment process the maximal tensile strength is 25.53 ± 3.94 MPa. For the type of woven twill before the alkali treatment the maximal tensile strength is 30.18 ± 7.26 MPa, after alkali treatment the maximal tensile strength is 35.15 ± 2.81 MPa.For plain weave type before alkali treatment strain is 2.29 ± 0.36% , after alkali treatment strain is 2.47 ± 0.25%. For this type of woven twill before alkali treatment strain is 2.27 ± 0.40%, after alkali treatment strain is 2.27 ± 0.40%.